Rapid antidepressant‐like effect of Fructus Aurantii depends on cAMP‐response element binding protein/Brain‐derived neurotrophic facto by mediating synaptic transmission. (12th October 2020) - Wu, Lei; Zhang, Tian; Chen, Ken; Lu, Chao; Liu, Xiang Fei; Zhou, Jia Ling; Huang, Yun Ke; Yan, Han; Chen, Ying; Zhang, Chun Jie; Li, Jun Feng; Shi, Shao Qi; et al.
Abstract : Several studies reported the relative antidepressant effects of Fructus Aurantii (FRA) with repeated treatment, the rapid antidepressant effects of FRA and the underlying mechanisms remained unclear. We, therefore, examined the rapid antidepressant actions of FRA in behavioral tests in mice and tested the underlying molecular mechanisms. We found FRA, like ketamine, reversed the behavioral deficits both in lipopolysaccharide(LPS)‐induced and learned helplessness (LH) models at 1 day after a single administration. FRA was also capable of increasing the expressions of protein kinase A/cAMP‐response element‐binding protein/brain‐derived neurotrophic factor (PKA/CREB/BDNF) signaling in hippocampus. Consistent with ketamine, FRA up‐regulated the expressions of GABAergic receptor (GAD67) and glutamatergic receptor 1 (GluR1) in mouse hippocampus both exposed to LPS and LH. Moreover, synaptic proteins such as postsynaptic density‐95 (PSD95) and synapsin1 were also up‐regulated by a single dose of FRA both in LH and LPS models, like ketamine. Finally, metadoxine (an antagonist of CREB) inhibited the antidepressant effects of FRA in tail suspension test (TST) and forced swimming test (FST) in LPS‐induced mice, which also blocked the phosphorylation of CREB and the expressions of neurotransmitters and synaptic molecules. Therefore, FRA had rapid antidepressant effects, which depended on PKA/CREB/BDNF pathway, subsequently regulated the downstream synaptic transmission.